2014
DOI: 10.2217/bmm.14.77
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin is a Useful Biomarker for the Prognosis of Critically Ill Septic Children

Abstract: MR-pro-ADM levels are good indicators of disease severity and show better reliability than PCT and CRP for predicting in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This biomarker was correlated with severity and could be used as a risk and prognostic stratifier with a higher positive predictive value for prognosis (in-hospital mortality) than PCT and CRP. (61) …”
Section: Introductionmentioning
confidence: 99%
“…This biomarker was correlated with severity and could be used as a risk and prognostic stratifier with a higher positive predictive value for prognosis (in-hospital mortality) than PCT and CRP. (61) …”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Jordan et al, 2014 (17) reported higher median values of MR-pro-ADM levels in ventilated patients or in cases needing inotropic support and in mortality cases. MR-pro-ADM levels at admittance showed a signi cant positive correlation with PRISM III score (r = 0.447; p < 0.001).…”
Section: Discussionmentioning
confidence: 94%
“…The mortality increased with increasing plasma ADM level. The studies in the literature suggested that increased plasma ADM level in the intensive care unit patients with sepsis was superior to procalcitonin and CRP that reflect infection status of the patients and offer a more valuable tool in predicting mortality (8)(9)(10)(11). In a study that compared survivors and non-survivors, plasma ADM levels were found to be higher in non-survivors compared to survivors (15).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies it was demonstrated that ADM level is superior to some other biomarkers, such as C-reactive protein (CRP), complete blood count (CBC), procalcitonin, pro brain natriuretic peptide (Pro BNP), acute physiology and chronic health evaluation II (APACHE II) score, in determining the mortality in sepsis (8)(9)(10)(11). Adrenomedullin is very highly expressed in adrenal gland in both zona glomerulosa and adrenal medulla, that's why we think that for elevation of plasma ADM level there should be adequate adrenal response (12,13).…”
Section: Adrenomedullin (Adm) Is a Peptide Initially Isolated From Phmentioning
confidence: 99%